Identification of Peptides in Aster tataricus by the Strategy of UHPLC-Q-TOF-MS/MS Combined with Molecular Network - CHEN Shi-lin;LIU Jie;FENG Meng-han;LI Yue-ting;JIA Zhi-xin;YANG Song;XIAO Hong-bin (Zhipu Xuebao, 2023)
The root of Aster tataricus L. f. has been widely used in the clinic for moistening lung, dispelling phlegm and relieving cough because of its significant therapeutic effects on respiratory diseases. The modern pharmacological research shows that the characteristic peptide components of Aster tataricus have anti-tumor, anti-oxidation, immunosuppression and other effects. So far, a total of 24 peptide components including cyclic pentapeptides (Astin A-I, K-P), cyclic tetrapeptides (Tataricins A-B), linear pentapeptides (Asterinin A-F) and linear dipeptide (Aurantiamide acetate) were isolated from Aster tataricus. Therefore, it is necessary to systematically and comprehensively explore more potential peptides in Aster tataricus, lays a foundation for later separation. At present, the molecular network technology based on LC-MS/MS has been widely used in qualitative characterization of chemical components of traditional Chinese medicine and efficient discovery of natural bioactive molecules, which can identify known compounds, analogues and new compounds. In this study, the method of ultra high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF-MS/MS) combined with molecular network was developed for systematically and rapidly analyzing peptides in 75% ethanol extract of Aster tataricus. Chromatographic separation was performed on an ACQUITY UPLC® HSS T3 column (100 mm×2.1 mm×1.8 μm). Acetonitrile and water solution were used as the mobile phase for gradient elution with the flow rate of 0.4 mL/min. The MS/MS analysis was carried out by the electrospray ionization (ESI) source at positive ion mode with scanning range of m/z 50-800, and then the data files were converted to the mzXML format by using MsConvert tools. The MS/MS data of 75% ethanol extract of Aster tataricus was converted on the platform of Global Natural Products Social Molecular Networking (GNPS), and the clusters were established according to the similarity of fragment ions, thus obtaining a molecular network. The network was exported and visualized using Cytoscape v3.8.0. Through the visual display of fragment ions, the aggregation and distribution of fragment ions were clearly displayed, and the interaction between molecules was intuitively searched. Thus, through the similarity of MS/MS data, the peptide components were related to form a network. The peptides in Aster tataricus were further identified according to the MS/MS fragmentation information of standard substances, accurate molecular weight and characteristic fragment ions. Finally, a total of 43 peptides from Aster tataricus were identified, including 31 cyclic peptides and 12 linear peptides, of which 16 may be potential new cyclic peptides and 8 may be potential new linear peptides. In general, the peptides in the Aster tataricus can be quickly, accurately and comprehensively identified by UHPLC-Q-TOF-MS/MS combined with molecular network, which provides a scientific basis for further research on the separation and purification of peptide components from Aster tataricus and elucidating its pharmacodynamic substances.